Antiviral Triterpenoid Saponins from the Roots of Ilex asprella - Zhou, Min; Xu, Min; Ma, Xiao-Xia; Zheng, Kai; Yang, Ke; Yang, Chong-Ren; Wang, Yi-Fei; Zhang, Ying-Jun (Planta Medica, 2012)
Two new sulfur-containing triterpenoid saponins, asprellanosides A (1) and B (2), were isolated from the roots of Ilex asprella, together with 10 known compounds (3–12). An in vitro anti-HSV-1 activity test of the isolates (1–4, 6–7, and 9–12) showed that only asprellanoside A (1) and oblonganoside H (6) exhibited anti-HSV-1 activity with TIC values of 0.14 and 0.18 mM, respectively.
Keywords: Ilex asprella; Aquifoliaceae; sulfur-containing triterpenoid saponins; asprellanosides A and B; antiviral